Violence against women: perceptions of nursing students' about the focus on the formation - Bruna Dedavid da Rocha; Maria Celeste Landerdahl; Laura Ferreira Cortes; Letícia Becker Vieira; Stela Maris de Mello Padoin (Universidad de Antioquia, 2015)
Objective. Get to know the nursing undergraduates perception, from a public university in southern Brazil, on the inclusion of the theme violence against women in the curriculum and about that thematic approach during graduation. Methodology. Descriptive exploratory qualitative research, made with 18 students of Nursing Graduation in Federal de Santa Maria University. Semi-structured interview was made and its data was submitted to thematic analysis. Results. From the undergraduates understanding, the theme integrates the curricular content in a punctual way and a reduced workload. There were found difficulties in the violence' identification and the actions to be developed. The participants suggest that the theme should be worked since the graduation' beginning, permeating the learning in collective health. Conclusion. The study shows the need to include violence as a transversal theme in curriculums in graduation courses of Nursing and Health.